(untitled) (Research, Society and Development, 2021)
Gingival recession occurs due to the migration of the gingiva in the apical direction, leading to compromising local aesthetics and root hypersensitivity. Connective tissue graft is the gold standard treatment in these cases improving both functional and aesthetics aspects.The purpose of this case is to report root coverage using the free connective tissue graftingtechnique (CTG) associated with topical application of active oxygen oral gel and mouthwash (blue®m). A 27-year-old female sought care with the main complaint of root hypersensitivity and the presence of gingival recession in the anterior region of the mandible. Clinical examination revealed the presence of type 1 gingival recession in the left mandibular central incisor. The treatment of choice was a modified graft (free connective graft). The graft and recipient bed received applications of blue®m oral gel. The patient was instructed to use blue®m mouthwash and blue®m oral gel after the surgery for 10 days. At 60 days, the patient showed satisfactory healing in the area of the free CTG, with gain of keratinized tissue and partial covering of the gingival recession. Free CTG with the support of the gel and the mouthwash with active oxygen release makes the technique viable, preventing graft necrosis and achieving root coverage and keratinized tissue.